PERFORMANCE ASSESSMENT AND EVALUATION: MEASURING SUCCESS AND ACHIEVEMENT - Obaob, Geronimo S.; Moneva, Jerald Cano-og (European Scientific Journal, ESJ, 2014)
This study used the quantitative approach in order to explore and focus on the preparation of appropriate and valid assessment tools relative to one’s teaching. The tri – dimensional work competence of man involves this particular competence in terms of the product or outcome of his effort. His action is ultimately directed to the learning of the students which need to be assessed as part of evaluation purposes and decision – making which requires immediate action in terms of instructional intervention and changes in order to cater to the needs of the students. A researcher – made questionnaire was formulated and distributed to the respondents to describe the general idea of what the teachers have done. The questionnaires consisted of ten statements were retrieved and the data were collated purposively. The data gathered were analyzed and subjected to statistical treatment such as average means and one – way ANOVA. Based on the results, the information reveals that preparation of appropriate and valid assessment tools matters in association with teacher performance.